The 2014 Academic College of Emergency Experts in India's INDO-US Joint Working Group (JWG) White Paper on “Developing Trauma Sciences and Injury Care in India” - Pal, Ranabir (Medknow Publications & Media Pvt Ltd, 2014)
It is encouraging to see the much needed shift in the understanding and recognition of the concept of “burden of disease” in the context of traumatic injury. Equally important is understanding that the impact of trauma burden rivals that of nontraumatic morbidities. Subsequently, this paradigm shift reinstates the appeal for timely interventions as the standard for management of traumatic emergencies. Emergency trauma care in India has been disorganized due to inadequate sensitivity toward patients affected by trauma as well as the haphazard, nonuniform acceptance of standardization as the norm. Some of the major hospitals across various regions in the country do have trauma care units, but even those lack protocols to ensure that all trauma cases are handled by those units, largely owing to lack of structured referral system. As a first step to reform the state of trauma care in the country, a detailed overview is needed to gain insight into the prevailing reality. The objectives of this paper are to thus weave a foundation based on the statistical and qualitative burden of trauma in the country; the available infrastructure of trauma care centers equipped to deal with trauma; the need and scope of standardized protocols for intervention; and most importantly, the application of these in shaping educational initiatives in advancing emergency trauma care in the country.